Applications of Hybrid Metal‐Dielectric Nanostructures: State of the Art. Issue 4 (17th January 2022) - Barreda, Ángela; Vitale, Francesco; Minovich, Alexander E.; Ronning, Carsten; Staude, Isabelle
Abstract : Enhancing the light‐matter interactions is important for many different applications like sensing, surface enhanced spectroscopies, solar energy harvesting, and for quantum effects such as nonlinear frequency generation or spontaneous and stimulated emission. Hybrid metal‐dielectric nanostructures have shown extraordinary performance in this respect, demonstrating their superiority with respect to bare metallic or high refractive index dielectric nanostructures. Such hybrid nanostructures can combine the best of two worlds: strong confinement of the electromagnetic energy by metallic structures and high scattering directivity and low losses of the dielectric ones. In this review, following a general overview of the properties of metal‐dielectric nanostructures, some of their most relevant applications including directional scattering, sensing, surface enhanced Raman spectroscopy, absorption enhancement, fluorescence and quantum dot emission enhancement, nonlinear effects, as well as lasing, are summarized. Abstract : In this review, the linear and nonlinear optical properties of hybrid metal‐dielectric nanostructures, which collectively combine strong electromagnetic energy confinement with high scattering directivity and low losses, are summarized. Relevant applications ranging from sensing, surface‐enhanced Raman spectroscopy, absorption and emission enhancement, and nonlinear effects (including laser) are also reviewed.